Differentiated Instruction in Araling Panlipunan for Junior High School - Balaus, Juana; Salcedo, Ph.D., Renato (Asian Journal of Multidisciplinary Studies, 2019)
This study aimed to determine the effectiveness of differentiated instruction in Araling Panlipunan for Junior High School. The grouped involved in the study were the experimental group where differentiated instruction was applied and control group where traditional method was used. Both groups were given pre-test before the experiment and post-test after the experiment. The instrument utilized in the study is a 50 item teacher made test. Involved in the study were the 33 Grade 8 students of Cabanaetan National High School, Mabini, Pangasinan. There were 17 student participants in experimental group and 16 student participant in control group. The study revealed that with differentiated instruction, the students’ participants in experimental group performed better than the student participant in control group and with differentiated instruction, the students performed better in Araling Panlipunan. Differentiated instruction has a better effect over non differentiated instruction. The significant recommendations include the following: The Araling Panlipunan teachers may use differentiated instruction as method of teaching to improve performance of students.;All teachers in Araling Panlipunan should undergo trainings that support and extol the virtues of Differentiated Instruction to enhance their teaching performance in classroom learning and School administrators should start the institutionalization of Differentiated Instruction in subjects like Araling Panlipunan to maximize the capability of the learners and teachers.